Numerical Investigation of Supersonic and Hypersonic Shock-Wave/Boundary-Layer Interactions - Bura, Romie Oktovianus; Graham T. Roberts; Yufeng Yao; Neil D. Sandham (Indonesian Journal of Aerospace, 2025)
Numerical simulations of 2-D supersonic and hypersonic laminar Shock-Wave/Boundary-Layer Interactions (SBLIs) were carried out by solving the Navier-Stokes (NS)equations using a compressible flow code over a wide range of Mach numbers and shockstrengths. The results obtained at Mach 2.0 and 7.73 were compared with experimentaldata. In addition, the numerical data were further analyzed using correlation laws derivedby previous researchers based on the free interaction concept, extended here to higherMach numbers. The results indicate that this concept is valid for separated laminar hypersonicflows with SBLIs. For interference heating, the correlation technique based on thewell-established power law relationship between peak heating and peak pressures yieldedencouraging results consistent with other correlations for laminar interference heating athypersonic speeds.